Self-assembled functionalized graphene nanoribbons from carbon nanotubes - Cunha, Eunice Paula Freitas (2015)
Graphene nanoribbons (GNR) weregenerated in ethanol solu-tion by unzipping pyrrolidine-functionalized carbon nanotubesunder mild conditions. Evaporation of the solvent resulted inregularfew-layer stacks of graphene nanoribbons observed bytransmission electron microscopy (TEM) and X-ray diffraction.The experimental interlayer distance (0.49–0.56 nm) was con-firmed by computer modelling (0.51 nm). Computer modellingshowedthat the large interlayer spacing (compared withgraphite) is due to the presence of the functional groups anddepends on their concentration.Stacked nanoribbons wereobserved to redissolve upon solvent addition. This preparationmethodcould allow the fine-tuning of the interlayer distancesby controlling the number and/orthe nature of the chemicalgroups in between the graphene layers.